2021
DOI: 10.20448/journal.509.2021.82.158.172
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computer Anxiety and Self-Efficacy on L2 Learners’ Self-Perceived Digital Competence and Satisfaction in Higher Education

Abstract: Low computer anxiety (CA) and high computer self-efficacy (CSE) levels are important affective factors that promote students' academic success in the current digital era. In an effort to understand their role in successful and effective participation in online learning environments for language learning purposes, the study investigated their effect on 331 undergraduate L2 learners' self-reported assessments of their digital literacy skills and on the level of satisfaction they express with the online component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
4
2
Order By: Relevance
“…This conclusion contradicts other studies that show a high degree of computer usage among students, particularly those in Generation X. (Katsarou, 2021;Kustono, 2021). Consequently, supporting pre-service teachers to become computer literate would assist them in increasing their effectiveness when employing information technology to provide optimal learning achievement.…”
Section: Discussioncontrasting
confidence: 90%
“…This conclusion contradicts other studies that show a high degree of computer usage among students, particularly those in Generation X. (Katsarou, 2021;Kustono, 2021). Consequently, supporting pre-service teachers to become computer literate would assist them in increasing their effectiveness when employing information technology to provide optimal learning achievement.…”
Section: Discussioncontrasting
confidence: 90%
“…Our results also reveal the relational analysis of teachers' computer self-efficacy on perceived ease of use and satisfaction. Generally, the higher the user's computer self-efficacy level, the more likely they feel comfortable with the new e-learning method (Katsarou, 2021). However, our results demonstrated that teachers' computer selfefficacy did not significantly impact their ease of use in online teaching.…”
Section: Major Findingscontrasting
confidence: 56%
“…In contrast to previous studies (Hung et al, 2010;Kuo et al, 2020), the present study results showed gender differences had a significant impact on online learning self-efficacy. In online learning, female students held higher levels of academic self-efficacy (Jan, 2015) and computer self-efficacy (Katsarou, 2021).…”
Section: Discussionmentioning
confidence: 97%